ACCESSIONS OF KYRGYSTAN TO THE CUSTOMS UNION: PRECONDITIONS, PROBLEMS, PROSPECTS - O. M. Evdokimova (MGIMO University Press, 2013)
The aspiration to associate in new integration structures, such as the CIS and EurAsEC, came to change to dezintegratsionny processes after disintegration of the Soviet Union. This article is devoted to a problem of development and deepening of degree of interrelation between CIS countries in such associations, as EurAsEC and EEP, to stages of formation of integration groups. The special attention is paid to one of the most topical issues – prospect of accession of Kyrgyzstan to the Customs Union. The following aspects are distinguished from favorable consequences of decision-making on accession for Kyrgyzstan:– sustainable development of economy and cooperation with other countries from Custom Union in long-term prospect; – attraction of additional investments into national economy;– liberalization of the legislation on migration, improvement of working conditions for migrants, growth of the budgetary income of host countries, formation of new workplaces;– economic and political support of Russia and other participating countries of EEP. As negative consequences are called probability of outflow of the qualified and unqualified labor from Kyrgyzstan and possible falling of Chinese goods' import because of cancellation of the simplified order of declaring. In the article it is spoken about the main measures accepted by the participating countries of the Custom Union and Kyrgyzstan for acceleration of inclusions process of the Kyrgyz republic in structure of the Customs union. The author comes to the conclusion that integration of Kyrgyzstan into the Customs union will lift economy of Kyrgyzstan which becomes a component of huge intercontinental economic association – the Custom Union and EEP - on new qualitative level. This factor will increase investment appeal of the country for foreign partners, becomes the guarantor of development of the long-term mutually advantageous relations.